The Role of Psychological Assets in Religious Education - Zahra Avatefi; Mohmmadjavad Fallah (پژوهش در آموزش معارف و تربیت اسلامی)
The purpose of the present study is to explain the role of psychological assets in religious education. The research method is descriptive-analytic and the results showed that psychological assets and its main components can be the inspiring source to continue religious activity and increases the chance of reaching inner peace, spiritual power to acquire divine attributes. In other words, features of psychological assets facilitate the way of becoming like God -as the goal of religious education- and provide necessary mental power and energy for people at difficulties, limitations, and obstacles to continue their activities. Components of psychological asset and religious education either directly or through a range of component meanings are interrelated; so that 4 components of psychological asset (self-efficiency, hopefulness, optimism, and resilience) can contribute to creating and continuing religious behaviors. As a result, people can prepare themselves to undertake action and achieve perseverance, resilience, and endurance (patience) to reach their goals.